2021
DOI: 10.1111/1751-2980.13037
|View full text |Cite
|
Sign up to set email alerts
|

Serum syndecan‐4 is associated with nonalcoholic fatty liver disease

Abstract: Objectives: The accelerated shedding of extracellular domains of syndecan-4 ( SDC4) is associated with central obesity and insulin resistance, while the association between serum SDC4 and nonalcoholic fatty liver disease (NAFLD) is unknown. We aimed to examine the association between SDC4 and NAFLD.Methods: Adults undergoing a health examination from 1 June 2019 to 31 December 2019 were enrolled. A diagnosis of NAFLD was made with an abdominal ultrasound. Logistic regression models and the receiver operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Recently, syndecan-4 was also published to be a serum marker of NAFLD (7) and also acts as a receptor of HCV (57), not only infecting the hepatocytes but also responsible for the submission of the virus from men to men infecting anal Langerhans cells (58). Besides syndecan-1, syndecan-4 also regulates the Wnt signaling (59).…”
Section: Overexpression Of Spock1 Coincides With Downregulation Of Sy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, syndecan-4 was also published to be a serum marker of NAFLD (7) and also acts as a receptor of HCV (57), not only infecting the hepatocytes but also responsible for the submission of the virus from men to men infecting anal Langerhans cells (58). Besides syndecan-1, syndecan-4 also regulates the Wnt signaling (59).…”
Section: Overexpression Of Spock1 Coincides With Downregulation Of Sy...mentioning
confidence: 99%
“…In the last 30 years, several publications proved the role of proteoglycans in the physiology and pathology of the liver. Although according to the literature syndecan-1 is the major heparan sulfate proteoglycan of the healthy liver, all four members of the family have been reported in increased amounts in various chronic liver diseases, such as liver fibrosis, cirrhosis (4,5), cholestasis (6), non-alcoholic fatty liver disease (NAFLD) (7), and cancer (8,9). Glypican-3 is a typical marker of hepatocellular carcinoma, detected not only in the tumor cells but also in the circulation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, univariate and multivariate analyses revealed that the age, N classification, and SDC4 expression were independent risk factors for the overall survival of PAAD patients. Existing studies highlighted the significant role of SDC4 as a potential marker for myocardial infarction [ 15 ], nonalcoholic fatty liver disease [ 16 ], and endothelial dysfunction in patients with resistant hypertension [ 17 ]. Moreover, we used GSEA and GSVA to screen the pathways associated with SDC4 enrichment, which mainly included spliceosome function, aminoacyl tRNA biosynthesis, proteasome activity, pentose phosphate pathway, base excision repair, mismatch repair, DNA replication, oxidative phosphorylation, mitotic spindle formation, epithelial-mesenchymal transition, TNFα signaling via NFKB, and G2M checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the mean and range of syndecan-4 levels in our patients overlapped with levels in healthy controls, albeit the latter in a low number, we evaluated the levels of serum syndecan-4 obtained using the same ELISA kit and sample material in published, historical controls ( Table 1 ). Although a number of studies have found significant changes in serum syndecan-4 in patient cohorts vs. healthy subjects, Table 1 demonstrates that there is a spread in the reported mean values for circulating syndecan-4 in control populations, ranging from 4.34 to 18.99 ng/mL [ 30 , 39 , 41 , 42 , 43 , 44 , 45 ]. Of note, syndecan-4 levels measured in healthy controls in one study are comparable to disease states in others.…”
Section: Discussionmentioning
confidence: 99%